Analysing behavioural differences of farm households: An example of income diversification strategies based on European farm survey data. (March 2017) - Weltin, Meike; Zasada, Ingo; Franke, Christian; Piorr, Annette; Raggi, Meri; Viaggi, Davide
Highlights: Data-based farm typologies reveal survival strategies of farm households. Six farm types in eleven diverse regional settings in Europe are identified. Strong variation in the willingness to diversify future income sources across types. Young households with organic production are most likely to diversify. Scenario of termination of financial support stimulates diversification behaviour. Abstract: Different forms of income diversification represent important strategies of farmers to either cope with the changing economic framework conditions or to valorise given territorial potentialities. Nevertheless, the decision to diversify economic activities on or off the farm will heavily depend on the agricultural business and household characteristics. Our study used a survey of 2154 farms from eleven European regions to identify distinct farm types in order to investigate differences regarding the willingness to diversify in the future. Two scenario situations with continuation (baseline) and without any market intervention ("No CAP") were tested. A factor and cluster analysis depicted six farm types both previously described and novel. The typology proved validity across all case studies, whereas single types occurred more frequently under specific site conditions. The six farm types showed strong variations in the stated future diversification behaviour. Young farm households with organic production are most likely to diversify activities particularly on-farm, whereas farm types characterised by intensive livestock holding and also already diversified and part-time farm households are least likely to apply this strategy. Results have further shown that under hypothetical conditions of termination of economic support by the Common Agricultural Policy (CAP) an increasing share of farmers – throughout all types – would apply income diversification, mainly off-farm diversification, as a survival strategy.